A Report on KDP Mandiri : An Analysis of Efforts to Replicate the Kecamatan Development Program - Basri, Nurlily (World Bank, Washington, DC, 2015)
Indonesia’s Kecamatan Development Project (KDP) began in 1998 and is implemented through the Ministry of Home Affairs, Community Development Office (PMD). KDP aims to alleviate poverty and improve local governance. The Project provides block grants of approximately USD 56,000 to USD 111, 000 to sub-districts (kecamatan). Villagers engage in a participatory planning and decision-making process to allocate those resources for their self-defined development needs and priorities. KDP is one of the largest community development projects in Indonesia, implemented in 29 of Indonesia’s 32 provinces. Field reports state that local governments in several parts of the country have initiated KDP replication or ‘spin off’ projects funded through their own budgets. These projects purport to replicate KDP to varying degrees. The main goal of this study is to examine in greater depth ten KDP replication schemes and to assess the extent to which they adopt certain principles and programmatic features of KDP. This study is important as an initial step to gain insight into how KDP’s principles and procedures may be influencing other government development projects especially in the areas of improved governance, community capacity building, and service delivery.